![\text{x = 7 and y = -1}](https://img.qammunity.org/2023/formulas/mathematics/college/hw75gtjc0d284xpzw1gmelzjj0ep6sapk5.png)
Here, we want to solve the system of equations by substitution
From the first equation, we can have an equation in terms of x
We have this as;
![x\text{ = -7y}](https://img.qammunity.org/2023/formulas/mathematics/college/udnuy9bf6q8mzdwjlt6mgms05pdxupv8wy.png)
Now, proceed to substitute this into the second equation
We have this as;
![\begin{gathered} 2(-7y)\text{ - 8y = 22} \\ -14y-8y\text{ =22} \\ -22y\text{ = 22} \\ y\text{ = }(22)/(-22)\text{ = -1} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ksjvab8ds7dlfv41t56kxlclyueuwaf7fn.png)
To get the value of x, what we have to do is to substitute the value of y in the equation we had for x
We have this as;
![\begin{gathered} x\text{ = -7y} \\ x\text{ = -7(-1)} \\ x\text{ =7} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1kwme3aq4rfe59zqqmxs7uf3xzgh00l9k6.png)